ANALISIS RISIKO KADAR GAS HIDROGEN SULFIDA (H2S) PADA MASYARAKAT SEKITAR PABRIK BIOETHANOL (Studi Kasus : Pabrik Bioethanol PT. Energi Agro Nusantara Kecamatan Gedeg Kabupaten Mojokerto Tahun 2018) - Laila Muzdalifatul A; Khambali .; Rachmaniyah . (GEMA LINGKUNGAN KESEHATAN, 2018)
Gempolkerep Village Gedeg Subdistrict Mojokerto District is a residential area that has a distance of ± 100m from Bioethanol Industry PT.Energi Agro Nusantara which is a producer of Ethanol and Biogas, thus the production process produces content of pollutant sources in ambient air one of them is hydrogen sulfide gas. The purpose of this study is to analyze the risk of exposure of H2S gas to communities living around the bioethanol plant i.e Gempolkerep Village, Gedeg Subdistrict, Mojokerto District. This research is a descriptive research using the design of Environmental Health Risk Analysis (ARKL) which was used to predict the size of the risks received by people living in Gempolkerep Village RT.8, RT.9, RT.12 and RT.13 with the sample used was a society with a range of age 20-25 years. Steps on ARKL were used to identify exposure patterns, community anthropometry and minimum H2S concentrations of H2S gas concentrations, on average, to the maximum, so as to determine risk characterization. The risk level was said to be safe when RQ ≤ 1, and the risk level was said to be unsafe when RQ 1.The results showed that from 4 point location overall average concentration of H2S gas 1,95 mg / m3, highest concentration 8,8 mg / m3, lowest concentration 0,4 mg / m3. The physical environment of the air obtained average air temperature was 30.6oC, the average air humidity was 55.1%, and the average wind speed was 1.0 m / s and the wind direction when the measurement blew from the West and South. Agents at risk of causing health problems to people in nearby areas close to the industry were H2S gas levels in the ambient air. The dose of H2S gas response was 0.000571 mg / m3. The entire community as respondents at the research location had a value of RQ 1. It can be concluded that all respondents who live around the bioethanol plant are said to be unsafe and at risk of health problems. So it is expected to be able to control and manage risk. Key words :  ARKL, Hydrogen Sulfide (H2S), Society